FREQUENCY OF FACTORS RELATED TO NON ADHERENCE IN PATIENTS WITH SCHIZOPHRENIA PRESENTING TO PSYCHIATRY DEPARTMENT AT CIVIL HOSPITAL KARACHI. - Bugti, Anaam; Sher, Zainab; Yousaf, Quratulain; Parwani, Anand (Journal of Pakistan Psychiatric Society, 2025)
Objective: To determine the factors associated with non-adherence to antipsychotic medication among adult patients with schizophrenia.Study design: Cross-sectional studyPlace and duration of study: The study was conducted at the Department of Psychiatry, Dr. Ruth K.M. Pfau Civil Hospital, Karachi in a period of six months.Methods: A total of 155 patients were recruited through consecutive sampling. Data on socio-demographic characteristics, clinical history and factors influencing non-adherence were collected using structured interviews.Results: The mean age of participants was 40.67 ± 11.44 years, with 63.2% being male. Non-adherence to medication was observed in 77.4% of patients, with significant contributing factors including adverse drug effects (61.5%), stigma (42.3%) and financial barriers (46.2%).Conclusion: Non-adherence to antipsychotic medications is alarmingly high among patients with schizophrenia in Pakistan, necessitating targeted interventions addressing economic, social and clinical challenges to improve adherence rates.Keywords: Non-adherence, Schizophrenia, Antipsychotic medication, Factors, Pakistan.